PENGARUH BUDAYA ORGANISASI DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN SELLERI INDONESIA - Azalia Novia Hesti Hesti; Siti Rahmawati (PT Naureen Digital Education, 2023)
Selleri Indonesia as a startup company that was established in 2021 is required to be able to compete in a competitive manner requiring good human resource management. Good human resources (HR) is the key to success in facing competition in the global era and plays a very important role in achieving company goals. This study aims to analyze the effect of organizational culture and employee engagement on the performance of Selleri Indonesia's employees. This study used primary and secondary data, which were analyzed quantitatively using descriptive methods and SEM-PLS. Based on the descriptive analysis of employee perceptions regarding organizational culture and employee engagement, it is included in the very good criteria. Based on the results of the SEM analysis, organizational culture has a positive and significant effect on employee engagement. Then, employee engagement has a positive and significant effect on employee performance. However, organizational culture has no significant effect on employee performance.